Assessment of the potential clastogenic/aneugenic risk of Casearia sylvestris extract using in vivo assays - Maistro, Edson Luis [UNESP]; De Andrade, Sergio Faloni; Puras, Marilane Aparecida [UNESP] (International Society of Cytology, 2007)
Casearia sylvestris (Flacourtiaceae) is a plant which grows in wild and has been widely used in folk medicine. In this study, clastogenic/aneugenic properties of Casearia sylvestris crude ethanolic extract were evaluated using in vivo chromosomal aberrations (CAs) and micronucleus (MN) assays in rodents. The animals were treated by gavage with 3 concentrations of the extract: 150, 300 and 500 mg/kg body weight. Bone marrow cells from Wistar rats were collected 24 h after having been submitted to the MN and CAs test. Peripheral blood cells from Swiss mice were collected 48 and 72 h after having been submitted to the MN test. The results show that C. sylvestris extract does not induce a significant increase in mean values for micronucleated polychromatic erythrocytes (MNPCE) in Swiss mice and Wistar rats, or CAs in rat bone marrow cells, at the 3 tested doses, indicating that the extract showed no clastogenic/aneugenic effects on chromosomes of the rodent cells tested. © 2007 The Japan Mendel Society.
Keywords: Casearia sylvestris; Chromosome aberration; In vivo; Micronucleus test; Animalia; Casearia; Flacourtiaceae; Mus; Rattus; Rattus norvegicus; Rodentia